Road Design Improvement Based On The Road Traffic Safety Assessment A case study at Jalan Kaliurang-UGM - , HENDRA NATA SAPUTRA; , Prof. Dr. Ir. Siti Malkhamah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The safety of road user is one of the main concerns of stakeholders such as government as regulator and road users. WHO reported that 1,2 million people died and about 20 to 50 million people suffer injuries on road in the world in every year. More than 90% of the worldâs fatalities in accident on road happened in developing countries including Indonesia. Road Safety Audit is needed to assess the road condition to improve the road safety. Three methods as tools of RSA were conducted, there are The Swedish Traffic Conflict Technique, RSA toolkit, and checklist. The observation and checklist for road safety condition was performed. The conflict technique was used to measure the conflict among road users and checklist was used to assess the geometric condition and safety facilitation in study area. The study area is located in road section at Kaliurang Street because there are many vehicles especially in peak hour. It connects the main road and supporting road and also many driveways or access roads around intersection which leads a lot of movement of vehicles and cause many conflict to occur. From observation and assessment of road safety, 33 conflicts occurred in one hour in the morning with 97% in serious level. Some problems that occurred in study area were inappropriate of geometric condition such as sight distance in approach of intersection and lack of safety facilitation. The improvement recommendations are focused on engineering area. The actions suggested in this thesis are to provide median or separator in site, proper signs and markings, and continuously cyclist and pedestrian path. It is expected to reduce 31 conflicts in study area and increase road safety.